2019
DOI: 10.12944/crnfsj.7.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide and Dicarbonyl Compounds Concentration in Honey Samples from Different Botanical Origins and Altitudes in the South of Saudi Arabia

Abstract: Different factors are known to affect the chemical constituents of the bees honey including the climate and the floral origin. The objective of this study was to investigate the effect of floral origin and altitude on some physiochemical properties of honey samples from the south western part of Saudi Arabia. The investigated physiochemical properties were the pH, conductivity and the concentration of hydrogen peroxide and dicarbonyl molecules. Fifteen Ziziphus spina christi honey samples were collected from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Siimilar to the conclusion of this study, We have concluded in another study that the altitude signi cantly affected the hydrogen peroxide percentage (Mohammed et al, 2019). Similar to our previous study nding (Mohammed et al, 2019), the altitude of this study signi cantly affected the concentration of dicarbonyl compounds in the Ziziphus and Acacia honey samples. However, the two studies were conducted in different seasons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Siimilar to the conclusion of this study, We have concluded in another study that the altitude signi cantly affected the hydrogen peroxide percentage (Mohammed et al, 2019). Similar to our previous study nding (Mohammed et al, 2019), the altitude of this study signi cantly affected the concentration of dicarbonyl compounds in the Ziziphus and Acacia honey samples. However, the two studies were conducted in different seasons.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to the effect of oral origin, this study reported a signi cant effect of the oral origin on the concentration of the dicarbonyl molecules (p-value= 0.007) and this conclusion was similar to the conclusion of our previous study in a different harvesting time (Mohammed et al, 2019). However, Arena et al (2011) classi ed different origin honey depeding on the diacrbonyl compounds and the phenols.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In Saudi Arabia, a lot of research was carried out on different aspects of honey. The effect of floral origin and altitude on physiochemical properties and concentration of vitamins was analyzed by Al-Mosa et al, 2019 , Mohammed et al, 2019 . Many researchers worked on antimicrobial ( Abdallah and Hamed, 2019 , Al-Hindi and Shehata, 2014 , Ansari et al, 2017a , Ghramh et al, 2019a , Ghramh et al, 2019b , Owayss et al, 2019 ), antioxidant ( Al-Hindi and Shehata, 2014 ), physicochemical properties including some quality parameters ( Ahamed et al, 2017 , Alqarni et al, 2014 , Alqarni et al, 2016 , Mesallam and El-Shaarawy, 1987 , Osman et al, 2007 ), mineral contents ( Al-Hindi and Shehata, 2014 , Alqarni et al, 2014 , Arida et al, 2012 , Osman et al, 2007 , Taha et al, 2018 ), floral pigments ( Alqarni et al, 2016 ), heavy metals ( Bazeyad et al, 2019 ), validation of botanical origins and geographical sources through ultraviolet spectroscopy and chemo metric analysis ( Ansari et al, 2018 ), and formation and biological activities of nanoparticles by using honey samples ( Al-Brahim and Mohammed, 2020 , Ghramh et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, honey is used as an antimicrobial agent because of its dicarbonyl compounds (methylglyoxal) and hydrogen peroxide content, and it acts as an antioxidant because it contains flavonoids, vitamins and minerals. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%